2019
DOI: 10.1002/cncr.31932
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing prostate cancer treatment decisions for African American and white men

Abstract: Background Prostate cancer racial disparities in mortality outcomes are the largest in all of oncology, and less aggressive treatment received by African American (AA) patients versus white patients is likely a contributing factor. However, the reasons underlying the differences in treatment are unclear. Methods This study examined a prospective, population‐based cohort of 1170 men with newly diagnosed nonmetastatic prostate cancer enrolled from 2011 to 2013 before treatment throughout North Carolina. By phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…In addition, strategies to mitigate toxicity through survivorship care are critical for improving long‐term outcomes. It should be noted that misalignment between perceived and actual cancer aggressiveness among Black men compared with White men potentially contributes to differences in treatment decisions 31 . In a prospective, population‐based cohort study, more African American men than White men with high‐risk prostate cancer perceived their cancers as not aggressive, and such perceptions were associated with a decreased likelihood of receiving treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, strategies to mitigate toxicity through survivorship care are critical for improving long‐term outcomes. It should be noted that misalignment between perceived and actual cancer aggressiveness among Black men compared with White men potentially contributes to differences in treatment decisions 31 . In a prospective, population‐based cohort study, more African American men than White men with high‐risk prostate cancer perceived their cancers as not aggressive, and such perceptions were associated with a decreased likelihood of receiving treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although access to health care has been known to be a main driver of health disparities and is also an important predictor of treatment behavior (Burt et al, 2018;Gordon et al, 2019;Noonan et al, 2016), our study shows that patients delayed treatment despite having health insurance coverage. A recent study by Gordon et al (2019) analyzed the North Carolina Prostate Cancer Comparative Effectiveness and Survivorship Study and reported that Black patients were more likely to consider cost (69.2%), treatment (69.2%), and recovery time (73.3%) as important therapeutic decision-making factors compared to White patients (34.9%, 33.8%, and 46.9%, respectively). Another study used SEER data to assess trends in PCa treatment from 2004 to 2014 concluded significant differences exist by patient age, insurance status, socioeconomic status (SES), and geographical residence (Burt et al, 2018).…”
Section: Discussionmentioning
confidence: 58%
“…In something so subjective and dependent on the individual perception of each patient and communication skills, it is highly likely that sociodemographic factors could influence patient choice and their urologist. Gordon et al (26) showed that > 50% Afro-Americans and 24% of white American studied, understood their disease as "non aggressive", even after a diagnosis of high risk disease. In our work, age was the only factor that individually influenced the choice of treatment, as patients over 70 years were virtually not subjected to RP (only 3.9%).…”
Section: Discussionmentioning
confidence: 99%